Role of cytokine levels in pathogen classification and prognosis of pediatric septic shock - Du, Guangyan; Huang, Haixin; Zhang, Ruichen; Liu, Chengjun; Fu, Yueqiang (Frontiers in Immunology, 2026)
BackgroundThe pathogenic role of inflammatory cytokine levels in children with septic shock has not been completely clarified. The aim of this study was to investigate the relationships between the early concentrations of inflammatory cytokines, pathogen classification, and 28-day mortality in children with septic shock.MethodWe retrospectively analyzed the early expression of cytokines in children admitted to the pediatric intensive care unit (PICU) of a tertiary pediatric hospital due to septic shock between July 2019 and September 2024.ResultsA total of 189 children with septic shock were included and 68 died within 28 days of hospitalization. The plasma levels of IL-6 (P = 0.001), IL-10 (P < 0.001), IFN-γ (P = 0.002), and TNF-α (P = 0.014) were significantly higher in the nonsurvivor group than in the survivor group. Multivariate Cox regression analysis revealed that the IL-6 level was an independent risk factor for 28-day mortality after controlling platelet count and lactate, lactate dehydrogenase, Hb, IFN-γ, and TNF-α levels. ROC analysis revealed the AUC values of the IL-6, IL-10, IFN-γ, and TNF-α levels were 0.64, 0.68, 0.64 and 0.61, respectively, and that the optimal cutoff values were 414.92 pg/ml, 29.66 pg/ml, 1.605 pg/ml and 0.725 pg/ml, respectively. According to these cutoff values, the survival curves of the groups with high levels of IL-6, IL-10, IFN-γ, and TNF-α differed significantly from those with low levels (p < 0.001, p < 0.001, p = 0.001, and p = 0.001, respectively). In children with positive fluid cultures, there was no statistically significant difference in cytokines levels between the gram-positive bacterial (G+) and gram-negative bacterial (G-) infection groups. However, in children with positive blood cultures, the levels of IL-6 (p = 0.005) and IL-10 (p = 0.003) were significantly higher in the G- group than in the G+ group.ConclusionElevated IL-6 and IL-10 levels are valuable for predicting 28-day mortality and identifying gram-negative bacteremia in pediatric patients with septic shock. IFN-γ and TNF-α levels also have significant value for predicting 28-day mortality. Moreover, the IL-6 level was an independent risk factor for 28-day mortality.